The Effect of Integrating Midwifery Counseling With a Spiritual Approach on Pregnant Women's Spiritual Experience: A randomized Controlled Trial - Nahid Moradi; Azam Maleki; Saeedeh Zenoozian (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Spiritual experience helps individuals to cope with stressful life situations. Objectives: The present study was to determine the effect of integrating midwifery counseling with a spiritual approach on pregnant women's spiritual experience. Methods: A randomized controlled trial study was conducted on 40 pregnant women who referred to Abhar health centers in 2019. For the experimental group, eight counseling sessions were held using a spirituality-oriented approach, and the control group received routine health care services. Data were collected using a spiritual experience questionnaire in three stages (namely before intervention, 28 weeks of pregnancy, and 36 weeks of pregnancy). The data were analyzed using descriptive statistics, the Chi-square test, the independent t-test, and ANCOVA at 95 % confidence level. Results: The comparison of the mean scores of spiritual experience in the experimental and control groups revealed that the scores were higher in the second and third trimesters. In this regard, the mean score of spiritual experience in the pre-intervention stage in the control group was 73.31, which decreased to 69.47 in the third trimesters. Meanwhile, the mean score of spiritual experience in the experimental group in the pre-intervention phase was 71.65, which increased by 84.15 in the third trimesters. The mean difference of spiritual experience scores was statistically significant between the two groups (p=0.001). Conclusion: Counseling along with a spiritual approach was effective in improving pregnant women's spiritual experience. , and it can be integrated with prenatal care package.